Dynamics of a Solidifying Icy Satellite Shell. Issue 5 (25th May 2021) - Buffo, J. J.; Meyer, C. R.; Parkinson, J. R. G.
Abstract: Ocean worlds have been identified as high‐priority astrobiology targets due to the link between life and liquid water. Young surface terrain on many icy bodies indicates that they support active geophysical cycles that may facilitate ocean‐surface transport that could provide observables for upcoming missions. Accurately interpreting spacecraft observations requires constraining the relationship between ice shell characteristics and interior dynamics. On Earth, the composition, physical characteristics, and bioburden of ocean‐derived ices are related to their formation history and parent fluid composition. In such systems, the ice–ocean interface, which exists as a multiphase mushy layer, dictates the overlying ice's properties and evolution. Inclusion of the physics governing these boundaries is a novel strategy in modeling planetary ices and thus far has been limited to 1D approaches. Here, we present results from 2D simulations of an archetypal ice–ocean world. We track the evolution of temperature, salinity, porosity, and brine velocity within a thickening ice shell enabling us to place improved constraints on ice–ocean world properties, including the composition of planetary ice shells, the thickness and hydraulic connectivity of ice–ocean interfaces, and heterogeneous dynamics/structures in the interfacial mushy layer. We show that stable eutectic horizons are likely a common feature of ice–ocean worlds and that ocean composition plays an important role in governing the structure and dynamics of the interface, including the formation of chemical gradient‐rich regions within the mushy layer. We discuss the geophysical and astrobiological implications of our results and highlight how they can be validated by instrument‐specific measurements. Plain Language Summary: Our solar system houses numerous ocean worlds that have the potential to harbor life. Typically, these oceans reside beneath a thick global icy shell. Accordingly, much of what we know about these bodies relies on interpreting spacecraft observations of their icy exteriors. To illuminate the interior properties and dynamics of these worlds, this requires an understanding of the relationship between internal processes and external observables. In ice–ocean environments, the relationship between ice and ocean properties is governed by complex dynamics occurring at the ice–ocean interface. This interface is characterized by a slushy mixture of ice and brine (a mushy layer), who's physical structure, fluid flow, and chemical dynamics determine the resultant ice properties. Very few models of planetary ices include these dynamics, and so far there only exists one‐dimensional models that do. Here, we present the first two‐dimensional model of planetary ices which includes the physics needed to accurately simulate the ice–ocean interface. We show that ice shell composition is governed by the two‐dimensional dynamics of the ice–brine mushy layer, that the thickness of this layer scales directly with ice shell thickness, and that gradient‐rich regions in the mushy layer could provide sheltered and chemically favorable environments for organisms. Key Points: The ice‐ocean interfaces of icy satellites likely exist as porous layers hydraulically connected to the underlying ocean Interstitial brines likely exist in regions of planetary ice shells that are above their eutectic temperature Thermochemical gradients in the porous basal layer of ice shells could provide a metabolic energy source for any potential organisms